PENGARUH KOMPETENSI KERJA TERHADAP KINERJA KARYAWAN DIMEDIASI KEMAMPUAN BERADAPTASI PADA PEGAWAI PERUM BULOG KANTOR CABANG CIREBON DAN INDRAMAYU - Luthfiyah Azizah Azmi; Asep Gunawan; Hevy Febriyansyah (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the effect of work competence on employee performance with the mediation of adaptability at Perum BULOG Cirebon and Indramayu Branch Offices. A quantitative approach was used with simple and multiple linear regression methods, and Sobel test for mediation testing. The results of the study show that work competence has a positive and significant impact on employee performance.. Additionally, work competence also positively influences adaptability, which in turn significantly impacts employee performance. Adaptability was found to mediate the effect of work competence on performance, indicating that employees with high adaptability can optimize their competencies to achieve better performance. This finding contributes to the development of human resource management, particularly in improving performance through effective competency and adaptability development.